Analysis of Women's Perception of Fiesta Contraceptives in Employees of PT. Pustaka Insan Madani - Puteri, Andanti Kartika; Nastain, M.; Siva, Nur (PT FORMOSA CENDEKIA GLOBAL, 2025)
One of the important things in the communication process, especially in Public Relations activities, is to understand the perceptions of the interlocutor. This study aims to see how the perceptions held by women regarding the same object, namely the Fiesta contraceptive device, with different backgrounds. This qualitative descriptive research collects data using interviews and documentation methods. The interviews involving 24 informants used direct, closed and informal interview techniques. Based on the 3 main components forming attitudes, namely cognitive, affective and conative components, then analyzed based on Perception Theory, this study concludes that differences in conditions, and one's background influence one's perceptions of one object, and in this study, conditions the most influential is marital status.